A 12‐week intervention with nonivamide, a TRPV1 agonist, prevents a dietary‐induced body fat gain and increases peripheral serotonin in moderately overweight subjects. Issue 5 (22nd February 2017) - Hochkogler, Christina M.; Lieder, Barbara; Rust, Petra; Berry, David; Meier, Samuel M.; Pignitter, Marc; Riva, Alessandra; Leitinger, Alina; Bruk, Anne; Wagner, Simone; Hans, Joachim; Widder, Sabine; et al.
Abstract : Nonivamide, a less‐pungent capsaicin analog, was studied for its potential as an antiobesity agent in a 12‐week human intervention study. The body composition was determined at the beginning and in the end of intervention. Moreover, plasma concentrations of satiating hormones were measured. Participants were instructed to drink the product formulation three times daily. After treatment, a group difference in body fat mass change and an increase in postprandial plasma serotonin concentrations were determined in the nonivamide group. Thus, we suppose that a daily intake of nonivamide might help to maintain a healthy body composition. Abstract : Scope: A bolus administration of 0.15 mg nonivamide has previously been demonstrated to reduce energy intake in moderately overweight men. This 12‐week intervention investigated whether a daily consumption of nonivamide in a protein‐based product formulation promotes a reduction in body weight in healthy overweight subjects and affects outcome measures associated with mechanisms regulating food intake, e.g. plasma concentrations of (an)orexigenic hormones, energy substrates as well as changes in fecal microbiota. Methods and results: Nineteen overweight subjects were randomly assigned to either a control (C) or a nonivamide (NV) group. Changes in the body composition and plasma concentrations of satiating hormones were determined at fasting and 15, 30, 60, 90, and 120 min after a glucose load. Participants were instructed to consume 0.15 mg nonivamide per day in 450 mL of a milk shake additionally to their habitual diet. After treatment, a group difference in body fat mass change (–0.61 ± 0.36% in NV and +1.36 ± 0.38% in C) and an increase in postprandial plasma serotonin were demonstrated. Plasma metabolome and fecal microbiome read outs were not affected. Conclusions: A daily intake of 0.15 mg nonivamide helps to support to maintain a healthy body composition.